3000 years of environmental change at Zaca Lake, California, USA - Dingemans, Theodore; Mensing, Scott A.; Feakins, Sarah J.; Kirby, Matthew E.; Zimmerman, Susan R. H. (Frontiers in Ecology and Evolution, 2014)
Climatic variations of the last few millennia can reveal patterns of variability beyond that recorded by the instrumental record. In this study we use pollen and sediments to generate a high resolution 3000 year record of vegetation and climate along the southern California coast. An increase in Pinus and Quercus pollen found in the top 100 years of the record is a result of known planting and fire suppression by the forest service. In the pre-historic record, a period of high Salix percentages and high pollen concentration from 500-250 cal yr BP represents the wettest period of the record and coincides with the Little Ice Age. We also find evidence for 3 warm periods between 1350 and 650 cal yr BP which are identified in the record by the presence of Pediastrum boryanum var. boryanum. The latter two of these periods, dating from 1070-900 and 700–650 cal yr BP correspond to Medieval Climatic Anomaly droughts identified in other records. In addition to these events, we identify a multi-centennial scale drought between 2700 and 2000 cal yr BP in Zaca Lake, corroborating evidence from across the Great Basin and extending the regional spread of this multi-centennial drought to southern California. Corresponding wetter conditions in the northwest indicate that the modern ENSO precipitation dipole also occurred during this persistent drought. Today this dipole is associated with La Niña conditions and we note a coincidence with intriguing evidence for a change in ENSO dynamics from marine records in the tropical Pacific. This dry period is remarkably persistent and has important implications for understanding the possible durations of drought conditions in the past in California.